Carbon-Free Power The Role of Small Modular (Nuclear) Reactors - Rao, Vikram (RTI Press Publication, 2022)
There is a new world order in electrical energy production. Solar and wind power are established as the low-cost leaders. However, these energy sources are highly variable and electrical power is needed 24/7. Alternative sources must fill the gaps, but only a few are both economical and carbon-free or -neutral. This book presents one alternative: small modular nuclear reactors (SMRs). The authors describe the technology, including its safety and economic aspects, and assess its fit with other carbon-free energy sources, storage solutions, and industrial opportunities. They also explain the challenges with SMRs, including public acceptance. The purpose of the book is to help readers consider these relatively new reactors as part of an appropriate energy mix for the future and, ultimately, to make their own judgments on the merits of the arguments for SMRs.